Clinical Urgency of After-Hours Presentations of Dogs and Cats to a Private Small-Animal Practice in Germany: A Retrospective Study of 4579 Visits - Leoni Wizenty; Marcus G. Doherr (Veterinary Sciences, 2026)
This descriptive study aimed to assess the urgency of after-hours emergency visits in a small-animal practice using a structured triage system, and to characterize the associated presenting conditions and treatments. Medical records of 3189 dog and 1390 cat visits presented between 1 January and 31 December 2021 to an advanced small-animal practice were retrospectively reviewed. Retrieved data included temporal characteristics of presentation, species, signalment, clinical diagnosis, diagnostics, and treatments. Visits were retrospectively categorized using a triage approach based on the five-point Manchester Triage System (MTS). More than half of all events were classified as non-emergency visits (blue and green triage); the proportion of red triage (immediate) cases was higher among feline than canine emergency presentations. The most frequent patient presentations to the after-hours emergency service occurred in spring and summer, with May and April being the busiest; holidays and Sundays had the highest average number of cases per day during the day shift. Causes of emergency visits were mainly due to gastrointestinal disorders in dogs (32.3%) as well as in cats (28.6%). Symptomatic therapy was the most common intervention in dogs (75.1%) and in cats (49.6%), followed by diagnostics (dogs 17.5%, cats 36.0%). These findings highlight the broad spectrum of after-hours emergency presentations in small-animal practice and the high proportion of non-emergency visits, and may inform future resource allocation and emergency service planning. However, as this was a retrospective single-center study, transfer of results to other settings must be done with caution.